Disuasión multiinestable. El poder igualador de la precisión y la guerra de salvas en la tercera era nuclear (Journal of the Spanish Institute for Strategic Studies, 2025)
The massive proliferation of long-range precision munitions is transforming strategic stability and the operational environment, introducing unprecedented challenges. This evolution adds to the debates on second and third-era nuclear deterrence, shaping a new stage characterized by the impact of these projectiles on strategic stability.Technological innovations are generating unprecedented strategic phenomena, altering the nature of war and giving rise to new forms of conflict. Although academic literature has addressed deterrence and strategic stability, it has overlooked certain aspects that this study aims to analyze.The article will review the first and second nuclear eras to contextualize the third, presenting original concepts such as the "equalizing power of precision," "salvo warfare," and "multi-unstable deterrence." Additionally, it introduces a previously unexplored strategic phenomenon: multi-unstable deterrence, which is key to the current dynamics of war.